Literature Review: Pemanfaatan Augmented Reality (AR) sebagai Media Pembelajaran Matematika Inovatif di Era Revolusi Industri 5.0 - Andi Trisnowali MS; Rusli, Rusli; Arifin, Sartika; Musa, Hastuty (Pendidikan Matematika FKIP Universitas Mataram, 2025)
In line with the development of the Industrial Revolution 5.0, which emphasizes the integration of human-centered, adaptive, and interactive technologies, the field of education is required to undergo a fundamental transformation in learning paradigms. One technological innovation that aligns with these characteristics is Augmented Reality (AR) as a learning medium. Based on the results of a literature review of SINTA-accredited national journals and Scopus-indexed international articles published within the last five to ten years, AR has demonstrated significant potential to enhance the quality of learning, particularly in mathematics education. Numerous studies indicate that the implementation of AR has a positive impact on students’ learning motivation, learning interest, and learning outcomes. AR enables the visualization of abstract concepts into more concrete representations, thereby facilitating deeper conceptual understanding and providing a more immersive and meaningful learning experience. Nevertheless, the implementation of AR in educational settings continues to face several challenges, including limited technological infrastructure, insufficient teacher competencies in utilizing AR-based media, and unequal access to digital devices. Therefore, systemic support is required to ensure that the integration of Augmented Reality as a learning medium can be implemented optimally and sustainably in the era of Industrial Revolution 5.0.